2017
DOI: 10.1038/tpj.2017.7
|View full text |Cite
|
Sign up to set email alerts
|

Significant variation between SNP-based HLA imputations in diverse populations: the last mile is the hardest

Abstract: Four SNP-based HLA imputation methods (e-HLA, HIBAG, HLA*IMP:02 and MAGPrediction) were trained using 1000 Genomes SNP and HLA genotypes and assessed for their ability to accurately impute molecular HLA-A, -B, -C, and –DRB1 genotypes in the Human Genome Diversity Project cell panel. Imputation concordance was high (> 89%) across all methods for both HLA-A and HLA-C, but HLA-B and HLA-DRB1 proved generally difficult to impute. Overall, less than 27.8% of subjects were correctly imputed for all HLA loci by any m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…44 The rs2395029 (G) variant in HCP5, a near perfect tag of HLA-B*57:01 (in Europeans), is used to screen for abacavir hypersensitivity. 45 The tag SNP utility remains relatively high (r ~ 0.92, 46 ) across globally diverse populations in the 1000 Genomes Project. Using PAGE and Global Reference Panel samples, we show that risk allele frequencies for rs2395029 rise above 5% in multiple large South Asian populations, and rise above 1% within some, but not all, admixed populations with Native American ancestry (Figure 4).…”
Section: Relevance Of Multi-ethnic Genetic Variation To Clinical Carementioning
confidence: 99%
“…44 The rs2395029 (G) variant in HCP5, a near perfect tag of HLA-B*57:01 (in Europeans), is used to screen for abacavir hypersensitivity. 45 The tag SNP utility remains relatively high (r ~ 0.92, 46 ) across globally diverse populations in the 1000 Genomes Project. Using PAGE and Global Reference Panel samples, we show that risk allele frequencies for rs2395029 rise above 5% in multiple large South Asian populations, and rise above 1% within some, but not all, admixed populations with Native American ancestry (Figure 4).…”
Section: Relevance Of Multi-ethnic Genetic Variation To Clinical Carementioning
confidence: 99%
“…This was evident in a study where HLA‐DRB1 imputation showed very low accuracy rate (<30%) for some alleles such as HLA‐DRB1*01:01, HLA‐DRB1*13:01, and HLA‐DRB1*15:01 belonging to the five most frequent HLA‐DRB1 alleles in the Finnish population when the reference material was from a large heterogeneous European population and not from the Finnish population . Low imputation accuracy for HLA‐DRB1 has also been described by other studies covering heterogeneous study cohorts or diverse ancestry groups . The reasons may be low HLA‐DRB1 tagging of the SNPs used due to the absence of the informative SNPs for HLA‐DRB1 region, inadequate numbers of reference SNPs and its poor representativeness for diverse populations …”
Section: Current Methods For Hla Typingmentioning
confidence: 67%
“…HLA‐DRB1*15:01 and HLA‐DQB1*06:02 have also been found to be resistance genes for HIV‐1 infection in Chinese and in European‐descent populations, respectively, corresponding to the protective genes in T1D . HLA‐DRB1*15:01 seems to be protective in Grave's disease and the haplotype DRB1*15:01‐DQA1*01:02‐DQB1*06:02 in European‐descent patients with autoimmune polyglandular syndrome and in Moroccan patients with pemphigus . In the Finnish population, we found the haplotype HLA‐B*07‐DRB1*15:01 to be protective for coronary artery disease .…”
Section: Hla and Disease Associationsmentioning
confidence: 65%
See 2 more Smart Citations